Pharmacokinetics and anti-ulcerogenic effects of Zuojin gastric floating bio-adhesive pellets in rats with acetic acid-induced gastric ulcer - Zhiqi Shi; Feng Xu; Tianli Xia; Zhenhua Bian; Sha Li (Elsevier, 2023)
Introduction: : Zuojin pills(ZP) have been shown to be effective in the treatment of gastric ulcer (GU); however, the efficacy of Zuojin gastric floating bio-adhesive pellets(ZFP) in GU treatment is yet to be evaluated. Methods: : The pharmacokinetics(PK) and protective effects of ZFP against acetic acid-induced GU was examined using rat models. Mass spectrometry(MS) analysis was performed using a TSQ LC-MS system. A total of 50male Sprague-Dawley(SD) rats were randomly assigned to five groups: normal, acetic acid-induced, positive control (rabeprazole, 2 mg/kg/day), ZP (500 mg/kg/day), and ZFP (500 mg/kg/day) groups, to elucidate the anti-ulcerogenic effect of ZFP. Results: : ZFP prolonged the residence time of the drug (MRT, 10.88 ± 0.93 h; T1/2, 42.83 ± 2.56 h) in rats and promote the effective absorption of the drug with obvious sustained-release properties. Compared with the control group, ZFP treatment for 7 d significantly increased the weight of the rats, significantly reduced ulcer index, increased gastric tissue Superoxide dismutase(SOD) activity, reduced gastric tissue Malondialdehyde(MDA) content, and increased serum IgA, IgM, IgG, and Interleukin-2(IL-2) levels. Additionally, histopathological analysis showed that ZFP treatment reduced inflammatory cell infiltration to mainly the mucosal layer, anda small amount of fibrous scar proliferative repair was observed in the mucosal defect area and the underlying inflammatory granulation tissue. Conclusion: : These results indicated that ZFP prolonged the residence time of the drug in rats with sustained-release properties and had an obvious protective effect against acetic acid-induced GU in rats.